Early diagnosis of Voh Winkel syndrome-inherited honeycombed hands and hearing loss - Anilkumar, Sukhada; Thomas, Irene Nirmala; Sukumaran , Vijayakumar (International Journal of Advances in Medicine, 2024)
Voh-Winkel Syndrome with approximately 50 cases reported in literature is a rare inherited Palmoplantar keratoderma characterised by honeycomb like hyperkeratosis, hearing loss or ichthyosis. It also features constricting fibrous bands that develop at the base of fingers/toes and later get strangulated to cause autoamputation called pseudoainhum. It is an autosomal dominant disorder with mutations in loricrin and connexin genes leading to hearing loss and ichthyosis variants respectively and manifests in infancy and becomes apparent later in childhood or adult life. Early diagnosis of this condition and management by multiple specialities given the associated features therefore becomes an absolute necessity. An emphasis on dermatological examination to manage hyperkeratosis using topical and systemic therapy, otorhinolaryngology to manage hearing loss as well as plastic surgery to alleviate symptoms arising due to the constriction bands is mandatory for effective management of this condition. Here we report a 22-year-old female patient who came with Palmoplantar keratoderma, bilateral hearing loss and pseudo-ainhum.